Analisis Kinerja Pegawai Melalui Leader Member Exchange dan Kompetensi dengan Kepuasan Kerja sebagai Mediasi (Studi Kasus pada ASN di Lingkungan Pemerintah Kabupaten Pemalang) - Shinta Solikhandari; Sulistiyani Sulistiyani; Gita Sugiyarti (Cakrawala Repositori IMWI, 2024)
This study aims to analyze the influence of Leader Member Exchange and competence on employee performance in Pemalang Regency Government, either directly or indirectly through job satisfaction as an intervening variable. The population used was all State Civil Servants at Diskominfo, BKD, Bapenda, BPKAD, and DPMPTSP Pemalang Regency, the size of the sample used was 155 respondents, with a proportionate stratified random sampling technique. The data source used is primary data, with a questionnaire data collection method. The analysis technique used is multiple linear regression analysis, path analysis and single test. The regression analysis results obtained that the Leader Member Exchange and competence have a positive effect on job satisfaction, and the Leader Member Exchange, competence, and job satisfaction have a positive effect on employee performance. Hypothesis test results show that (1) Leader Member Exchange has a positive and significant effect on job satisfaction, (2) Competence has a positive and significant effect on job satisfaction, (3) Job satisfaction has a positive and significant effect on employee performance, (4) Leader Member Exchange has a positive and significant effect on employee performance, and (5) Competence has a positive and significant effect on employee performance. The results of the path analysis and sobel test show that job satisfaction can mediate or strengthen the influence of the Leader Member Exchange on employee performance, and job satisfaction can mediate or strengthen the influence of competence on employee performance.